Robotic inspection and automated analysis system for advanced manufacturing - Mikhail, Maged; Abed, Karen (IAES International Journal of Robotics and Automation (IJRA), 2023)
Companies have developed various systems to improve their processes. These processes’ focus has been to produce more quantity in less time. To accomplish this task, it is important to also consider defects. Defective products can cause delays in the production line, rework, and the loss of money, time, and resources. This project focused on developing an integrated inspection system. Previous research has been done regarding types of vision systems, in-line inspections, and feedback data collection. A programmable logic controller (PLC) was used to control when the conveyor belt starts and stops. When the object has reached a certain position, the camera detects if the object passed or failed the process. If the object fails, the robot will pick up the bottle and take it out of the line. Human-machine interface (HMI) was also integrated, which shows how many bottles have passed and failed with a light that will indicate if a certain object has passed or failed. Feedback from the inspection process can help solve potential issues from different machines and processes. The testbed was designed, integrated, and tested in the paper to perform a feedback analysis for the production line. The setup consisted of MicroLogix PLC, Fanuc robot LR Mate 200iD and Cognex camera.